Asynchronous Online Learning: Top-down and Bottom-up Processes for Listening Practices - Utomo, Slamet; Sulistyowati, Titis (Language Circle: Journal of Language and Literature, 2022)
Asynchronous learning can be the best choice to provide a new learning environment during the pandemic situation because asynchronous environments treat students as autonomous learners. Students can learn with no time limitation, and students can learn on online activities independently. E- EFL learning can be done by adopting asynchronous learning. This study examined the asynchronous learning effect on the students listening skills. This learning also adopts the principle of top-down and bottom-up listening strategies. Teachers modify and develop the listening activities to meet the students' needs by using the Google Form link. In this research, the researchers introduce news items as listening resources. The researchers conducted this study to study the listening proficiency of first-semester students before and after implementing the top-down and bottom-up listening processes in asynchronous learning environment. This experimental research is one group pretest and posttest only. To determine the effectiveness of the asynchronous top-down and bottom-up listening processes, the researchers used the Wilcoxon test to analyze the significant difference between the pre and posttest. The researchers conclude that the top-down and bottom-up process in listening is suitable for teaching news items. The paired sample test proved a significant difference between the pre and posttest data which then indicates that the students' listening comprehension on news items increases significantly. Asynchronous learning offers students many advantages while they are practicing online listening. Problems and listening difficulties challenge the teachers to develop the learning management for further achievement.